Features of Professing Interest Young People Are to Audiovisual Mass Medias - Mitlosh, A. (Psychological Prospects Journal, 2013)
This publication analyzes the current studies of expression of interest to the media, the conditions of formation of interest to the media, especially the impact of print and audiovisual media.